2022
DOI: 10.1002/smll.202107444
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Uranium Single Atom from Radioactive Wastewater for Enhanced Water Dissociation and Hydrogen Evolution

Abstract: As a common nuclide in radioactive wastewater, uranium (U) is generally treated by landfill, which induces the massive abandonment of uranium resources. In this work, a pulse voltammetry method for the synthesis of U single atoms on MoS 2 (U/MoS 2 ) nanosheets from radioactive wastewater for the electrocatalytic alkaline hydrogen evolution reaction (HER) is reported. The mass loading of U single atoms is facilely controlled with high selectivity for coexisting ions in radioactive wastewater. In the electrolyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 58 publications
3
16
0
Order By: Relevance
“…The HRTEM image in Figure S19a at fully discharged state shows the generation of MnOOH. The reversible shift of the binding energy of O Mn−OH during the charging and discharging process is related to the H + de‐intercalation and intercalation process, because the H + storage density decreases with the H + de‐intercalation during the charging process, and the binding energy of H + will increase, [26] thus making O Mn−OH shift to a higher position. The discharging process is the opposite.…”
Section: Resultsmentioning
confidence: 99%
“…The HRTEM image in Figure S19a at fully discharged state shows the generation of MnOOH. The reversible shift of the binding energy of O Mn−OH during the charging and discharging process is related to the H + de‐intercalation and intercalation process, because the H + storage density decreases with the H + de‐intercalation during the charging process, and the binding energy of H + will increase, [26] thus making O Mn−OH shift to a higher position. The discharging process is the opposite.…”
Section: Resultsmentioning
confidence: 99%
“…[42] In addition, a downshift of the binding energy for Se 3d peaks may also result from the bonding of Ru to the Se edge of MoSe 2 . [43] Moreover, the Mo 3d and Se 3d signals for CC@MoSe 2 @Ru presented the same binding energy location as CC@MoSe 2 , revealing the weak electronic and coordinate interaction between Ru NPs and the MoSe 2 surface, which may not lead to the transition of MoSe 2 . This result agreed with the Raman analysis.…”
Section: Morphological and Structural Characterizationsmentioning
confidence: 89%
“…15 For instance, Meek et al reported semiconductor devices using UO 2 16 and Wang et al designed a uranium-based catalyst, which exhibited a superior HER, 17 and Liu et al fabricated a uranium single atom-based electrode for the HER. 18 Lin et al employed the UO 6 catalyst to enhance the OER. 19 However, less work has been carried out on the electrocatalytic applications of uranium metal complexes, although they have been the major source of nuclear energy.…”
Section: E 4ohmentioning
confidence: 99%
“…Apart from this, the organouranium complexes have been recently explored as potential materials in catalysis because of their attractive properties such as gas adsorption, nonlinear optics, and photoelectrochemical activity . For instance, Meek et al reported semiconductor devices using UO 2 and Wang et al designed a uranium-based catalyst, which exhibited a superior HER, and Liu et al fabricated a uranium single atom-based electrode for the HER . Lin et al employed the UO 6 catalyst to enhance the OER .…”
Section: Introductionmentioning
confidence: 99%